PSYCHOLOGİCAL MANİFESTATİONS OF EMOTİONAL EXHAUSTİON: THE İNFLUENCE OF VARİOUS FACTORS ON EXHAUSTİON - Rzayeva, Jala (Revista Gênero e Interdisciplinaridade, 2025)
The study is devoted to the study of the manifestations of emotional exhaustion. The study showed that the level of emotional exhaustion of people at different stages of professionalism is different, and this is a factor that deserves serious attention. In modern psychology and pedagogy, the tendency to determine the relationship between a person’s mental state and his behavior outside the professional environment has been widely studied. Studies show that the impact of emotional exhaustion on non-professional behavioral reactions is reflected in the organizational level of personality activity. Emotional exhaustion is manifested in teachers and students in higher vocational education in a wider range, which, if not prevented, can lead to serious problems. Teachers suffer from excessive workload, and the increase in the number of lessons associated with the transition from school to university and the increase in the number of social roles make it difficult for students to cope. Facts show that the presence of stages of tension, resistance and exhaustion can be considered important manifestations of emotional exhaustion.